Student perspectives on the nature of pre-university career support : an urban/rural comparison - Pearce, Gregory D., 1964- (1998)
Thesis (M. Ed.)-- Memorial University of Newfoundland, 1998. Education Bibliography: leaves 73-81. This study was designed to explore and compare the career related needs of rural and urban youth upon entering a post-secondary institution. Subjects were 101 university students who had completed at least their first year of university study. Subjects were asked to complete a questionnaire developed from a list of perceived career related needs identified in a study by Jeffery and Lehr (1993). While few significant urban/rural differences were found, a number of unexpected outcomes related to the career preparedness of all youth were noted. In addition, several areas needing further study are discussed.